Risk of Periodontitis in Patients with Gastroesophageal Reflux Disease: A Nationwide Retrospective Cohort Study - Li, Xin; Chaouhan, Hitesh Singh; Wang, Yao-Ming; Wang, I-Kuan; Lin, Cheng-Li; Shen, Te-Chun; Li, Chi-Yuan; Sun, Kuo-Ting (Biomedicines, 2022)
Background: Gastroesophageal reflux disease (GERD) is the most common digestive clinical problem worldwide that affects approximately 20% of the adult populations in Western countries. Poor oral hygiene has been reported to be associated with GERD as an atypical clinical complication. However, evidence showing the relationship between GERD and the risk of periodontitis is less clear. The present study aimed to use a retrospective cohort study design to further clarify the association between GERD and the subsequent risk of periodontitis. Methods: The risk of periodontitis in patients with GERD was investigated by analyzing epidemiological data from the Taiwan National Health Insurance Research Database from 2008 to 2018. We selected 20,125 participants with a minimum age of 40 years in the GERD group and 1:1 propensity-matched these with non-GERD individuals by sex, age, and comorbidities. The incidence of periodontitis was determined at the end of 2018. A Cox proportional hazards regression model was used to evaluate the risk of periodontitis in patients with GERD. Results: The overall incidence rate of the periodontitis risk was 1.38-fold higher (30.0 vs. 21.7/1000 person years, adjusted hazard ratio (aHR) = 1.36, 95% confidence interval (CI) = 1.28–1.45) in patients with GERD than in those without GERD. After stratified analyses for sex, age, and comorbidity, patients with GERD had a higher risk of periodontitis for age (aHR = 1.31, 95% CI = 1.20–1.42 for 40–54 years and aHR = 1.42, 95% CI =1.28–1.57 for 55–69 years), sex (aHR = 1.40, 95% CI = 1.28–1.54 for men and aHR = 1.33, 95% CI = 1.23–1.45 for women), and presence (aHR = 1.36, 95% CI = 1.27–1.45) and absence (aHR = 1.40, 95% CI = 1.21–1.62) of comorbidity than those without GERD. Among the GERD cohort, the risk for periodontitis was increased with an increasing number of emergency room visits (≥ 1 vs. <1, aHR = 5.19, 95% CI = 2.16–12.5). Conclusions: Our results revealed that patients with GERD have a higher risk of periodontitis development than those without GERD. Clinicians should pay more attention to identifying and managing periodontitis in patients with GERD.